Environmental Education for children following the 2030 Agenda: Mobilizing on ocean biodiversity (Research, Society and Development, 2023)
The United Nations 2030 Agenda is a global plan to raise awareness among citizens about the importance of Sustainable Development to care for life on Planet Earth. Considering the urgent need to promote environmental initiatives that raise awareness among children and instill a sense of environmental sustainability from an early age, this article aims to highlight a ludic didactic sequence aimed at informing basic education students about the UN Sustainable Development Goals (SDGs), emphasizing the issues of Pollution and Marine Life, linked to SDG 14. By connecting Higher Education with Basic Education, this approach directs a crucial attention to the latter. The action's facilitators provided interactions for the children with the focal theme, fostering positive attitudes of belonging towards the ocean's animal diversity. The records of the conducted and analyzed observations revealed that the school needs more intensive efforts to impart fundamental knowledge about environmental issues to the children, at a time when global warming and biodiversity loss are increasingly impacting living beings.